2009
DOI: 10.1210/jc.2009-1134
|View full text |Cite
|
Sign up to set email alerts
|

A Reappraisal of Diagnosing GH Deficiency in Adults: Role of Gender, Age, Waist Circumference, and Body Mass Index

Abstract: The results of the current study show that waist circumference and BMI are the strongest predictors of GH peak after GHRH+ARG followed by age. However, the old cutoff value of 9.0 microg/liter was in line with the new cutoffs in 95% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 34 publications
4
50
0
Order By: Relevance
“…Our data confirmed the mutual relationship between GHD and adiposity, since a strong negative correlation was found between VAI and GH peak at diagnosis, in agreement with previous studies that demonstrated that GH peak after GHRH plus arginine depends more on WC than on BMI [39]. Ideally, the possibility to use one single value representingat the same time BMI and WC could be very useful, and in this light the VAI might represent a useful tool.…”
Section: Discussionsupporting
confidence: 91%
“…Our data confirmed the mutual relationship between GHD and adiposity, since a strong negative correlation was found between VAI and GH peak at diagnosis, in agreement with previous studies that demonstrated that GH peak after GHRH plus arginine depends more on WC than on BMI [39]. Ideally, the possibility to use one single value representingat the same time BMI and WC could be very useful, and in this light the VAI might represent a useful tool.…”
Section: Discussionsupporting
confidence: 91%
“…While the influence of a pathological GH axis on lipid levels was analyzed in numerous clinical studies (10,14,16,17,18,19,20,21,22,23,33,34,35), observational studies in general population samples are scarce and longitudinal analysis is missing. To the best of our knowledge, the present study is the largest populationbased study using an IGF1 and IGFBP3 measurement in line with recommendation of the Keswick consensus conference to close this gap.…”
Section: Discussionmentioning
confidence: 99%
“…The older age of these subjects might be a reason for the conflicting results and further a limiting factor for a general conclusion. With respect to patient studies, low and high IGF1 levels outside the reference range are associated with lower HDL cholesterol (10,14,19,20,21,23,33). An interesting observation was made among GHD patients who discontinued their GH replacement therapy.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…If BMI-adjusted cutoff values are not used, a higher proportion of patients will be classified as GHD. In addition, age-adjusted cutoff values have recently been reported for the GHRH-arginine test (31).…”
Section: Discussionmentioning
confidence: 99%